Do Hospitals That Volunteer for Joint Replacement Bundled Payments Save More Money Than Those Required to Participate?. (15th September 2021) - Liao, Josh; Gupta, Atul; Zhao, Yueming; Zhu, Jingsan; Cousins, Deborah; Navathe, Amol
Abstract : Research Objective: Medicare has used both voluntary and mandatory programs to engage hospitals in joint replacement bundles. Starting in 2013, hospitals voluntarily joined the Bundled Payments for Care Improvement (BPCI) program. In 2016, Medicare randomly assigned hospitals in 67 of 196 metropolitan statistical areas (MSAs) to mandatory bundled payments under the Comprehensive Care for Joint Replacement (CJR) program. Because the CJR mandate applied to both hospitals with and without prior experience in BPCI, Medicare created the unique opportunity to compare performance between hospitals that voluntarily self‐selected into bundled payments (i.e., chose to participate in BPCI prior to CJR) versus hospitals that did not (i.e., did not participate in BPCI prior to CJR). Study Design: Our study leveraged the randomized design of CJR and compared CJR MSAs to non‐CJR MSAs weighted by strata and using an intention‐to‐treat approach. We used 2011–2017 Medicare claims and generalized linear models with hospital fixed effects to conduct a difference‐in‐differences analysis evaluating patients in CJR‐mandated markets undergoing joint replacement at hospitals with BPCI experience ( voluntary hospitals ) versus without BPCI experience ( mandatory hospitals ) prior to CJR. Like prior work, our comparison group consisted of patients undergoing joint replacement at hospitals in non‐CJR markets without BPCI experience, i.e., hospitals without any joint replacement bundle experience ( non‐participant hospitals ). The study outcome was post‐discharge institutional spending. Standard errors were clustered by MSA. Population Studied: 1, 568, 567 Medicare fee‐for‐service beneficiaries hospitalized at 92 voluntary, 759 mandatory, and 911 non‐participant hospitals. Principal Findings: Voluntary hospitals tended to be larger than mandatory and non‐participant hospitals, and more likely to be non‐profit, teaching institutions. Voluntary hospitals also had higher financial margins and cared for lower proportions of Medicare/Medicaid dual‐eligible patients than other hospital types. In adjusted analyses, voluntary hospitals exhibited differentially lower post‐discharge institutional spending compared to non‐participants hospitals (adjusted difference‐in‐differences [aDID] ‐539, 95% CI ‐823 to ‐255, p < 0.001). Mandatory hospitals also had differentially lower post‐discharge institutional spending than non‐participant hospitals (aDID ‐410, 95% CI ‐645 to ‐174, p = 0.001). Changes in post‐discharge institutional savings were not statistically significantly different between voluntary and mandatory hospitals (p = 0.34). Conclusions: Hospitals that both voluntarily and involuntarily accepted bundled payments achieved joint replacement savings. We did not find evidence that voluntary participants achieved greater savings. These are the first empirical data for bundled payments – and value‐based payment reforms more generally – comparing financial performance between voluntary and mandatory participants. Implications for Policy or Practice: This analysis has two major policy implications. First, it highlights the potential for policymakers to achieve payment reform goals by using both voluntary and mandatory programs, both of which possess benefits and drawbacks. By demonstrating that mandatory hospitals did not generate smaller savings than voluntary hospitals, our analysis also counters the idea that voluntary programs are more advantageous than mandatory ones because they can generate more savings. Second, it highlights that CJR effects were likely underestimated by Medicare and others given that BPCI predated and drove changes in joint replacement care prior to CJR. Primary Funding Source: National Institutes of Health.